Mathematical Analysis Of Improving The Use And Creation Of Didactic And Exhibition Tools In Biology Teaching (Texas Journal of Agriculture and Biological Sciences, 2024)
Improving the methodology of using didactic-visual tools in the process of teaching biology is one of the current issues.Despite the fact that didactic materials are actively used by teachers in practice, they often use didactic materials mainly to monitor students' knowledge